2014
DOI: 10.1002/joc.4219
|View full text |Cite
|
Sign up to set email alerts
|

Precursor synoptic‐scale disturbances associated with tropical cyclogenesis in the South China Sea during 2000–2011

Abstract: Precursor synoptic disturbance characteristics associated with 35 tropical cyclone (TC) genesis events in the South China Sea (SCS) during 2000-2011 were examined. All genesis events occurred between May and December. Six types of precursor synoptic disturbances are identified, and their low-level composite patterns are constructed. They are synoptic-scale wave train (29%), TC energy dispersion (14%), Pacific easterly wave (9%), Borneo vortex (11%), TC southwesterly shear induced vortex (23%), and others (14%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…TC track direction is one of the major factors that should be included in TC landfall prediction (Wang and Chan 2002;Liu and Chan 2003;Yang et al 2015a, b). Previous studies have shown that the interannual and interdecadal variability of TC activity in the western North Pacific (WNP) is closely related to the El Niño-Southern Oscillation (ENSO), Pacific Decadal Oscillation (PDO) and East Asian monsoon variability (Wang et al 2012;Yuan et al 2014). As the most important mode in the topical air-sea interaction, ENSO has a strong influence on the interannual variability of TC activity (Saunders et al 2000;Sobel and Maloney 2000;Wang and Chan 2002;Wu et al 2005;Camargo and Sobel 2005;Chan 2006;Zhang et al 2012a, b;Wang et al 2014;Kim et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…TC track direction is one of the major factors that should be included in TC landfall prediction (Wang and Chan 2002;Liu and Chan 2003;Yang et al 2015a, b). Previous studies have shown that the interannual and interdecadal variability of TC activity in the western North Pacific (WNP) is closely related to the El Niño-Southern Oscillation (ENSO), Pacific Decadal Oscillation (PDO) and East Asian monsoon variability (Wang et al 2012;Yuan et al 2014). As the most important mode in the topical air-sea interaction, ENSO has a strong influence on the interannual variability of TC activity (Saunders et al 2000;Sobel and Maloney 2000;Wang and Chan 2002;Wu et al 2005;Camargo and Sobel 2005;Chan 2006;Zhang et al 2012a, b;Wang et al 2014;Kim et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The Madden-Julian Oscillation (MJO) is known to influence cyclogenesis across the tropics [4][5][6][7][8][9][10] . In the north Indian Ocean also, the genesis and evolution of the cyclone is generally associated with the MJO 11,12 .…”
mentioning
confidence: 99%
“…Wang et al (2007) found that during southwest monsoon period, as sea surface temperature and relative humidity well favor the TCG in the SCS, positive lower-tropospheric vorticity and weak vertical wind shear are indicative to the locations of TCG. Yuan et al (2015) summarized six types of TCG in the SCS from the samples in 2000-2011: 1) synoptic-scale wave train (SWT), 2) TC energy dispersion (TCED), 3) Pacific easterly wave (EW), 4) Borneo vortex (BV), 5) TC southwesterly shear induced vortex (TCSV), and 6) others. Compared with the WNP TCs in the main Frontiers in Earth Science frontiersin.org developing region, the BV and TCSV are the two unique TCG types in the SCS.…”
Section: Introductionmentioning
confidence: 99%